Creating a Novel Video Vignette Stroke Preparedness Outcome Measure Using a Community-Based Participatory Approach. Issue 4 (July 2015) - Skolarus, Lesli E.; Murphy, Jillian B.; Dome, Mackenzie; Zimmerman, Marc A.; Bailey, Sarah; Fowlkes, Sophronia; Morgenstern, Lewis B.
Evaluating the efficacy of behavioral interventions for rare outcomes is a challenge. One such topic is stroke preparedness, defined as inteventions to increase stroke symptom recognition and behavioral intent to call 911. Current stroke preparedness intermediate outcome measures are centered on written vignettes or open-ended questions and have been shown to poorly reflect actual behavior. Given that stroke identification and action requires aural and visual processing, video vignettes may improve on current measures. This article discusses an approach for creating a novel stroke preparedness video vignette intermediate outcome measure within a community-based participatory research partnership. A total of 20 video vignettes were filmed of which 13 were unambiguous (stroke or not stroke) as determined by stroke experts and had test discrimination among community participants. Acceptable reliability, high satisfaction, and cultural relevance were found among the 14 community respondents. A community-based participatory approach was effective in creating a video vignette intermediate outcome. Future projects should consider obtaining expert and community feedback prior to filming all the video vignettes to improve the proportion of vignettes that are usable. While content validity and preliminary reliability were established, future studies are needed to confirm the reliability and establish construct validity.